DEVELOPMENT OF A DIGITAL SHARIA FINANCIAL READINESS MODEL TO IMPROVE THE PERFORMANCE OF MSMES USING SEM-PLS - Gilang Ganjar Amrih; Dadang Romansyah; Zaldy Suhatman; Donny Indradi; Sev Rahmiyanti (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2026)
The expansion of digital technologies has transformed the Islamic financial landscape and generated new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to strengthen operational effectiveness, improve access to financial resources, and enhance business sustainability. Although a wide range of Islamic digital financial services are currently available, their successful utilization largely depends on the preparedness of MSME actors to engage with digital financial systems. This study proposes a Digital Sharia Financial Readiness model by integrating Islamic financial literacy and Islamic fintech literacy as determinants of MSME performance. A quantitative research approach was adopted, and the conceptual model was developed through a synthesis of twenty-eight prior studies focusing on Islamic finance, Islamic fintech, financial inclusion, digital transformation, and MSME development. The proposed framework identifies Islamic financial literacy and Islamic fintech literacy as antecedent variables, Digital Sharia Financial Readiness as a mediating construct, and MSME performance as the outcome variable. The findings indicate that both literacy dimensions contribute to the enhancement of digital readiness, which subsequently supports improved business performance. Furthermore, digital readiness serves as a mechanism through which literacy competencies are translated into organizational outcomes. The study emphasizes the strategic role of digital readiness in facilitating the adoption of Islamic financial technologies and supporting sustainable MSME growth in the digital era.